Akumulasi dan Distribusi Bahan Kering pada Beberapa Kultivar Kacang Tanah - Heni Purnamawati; Roedhy Poerwanto; Iskandar Lubis; , Yudiwanti; Sri Astuti Rais; Ahmad Ghozi Manshuri (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> This research was carried out in April–September 2007. The research objective was to study the dry matter distribution pattern of several peanut cultivars. Twenty cultivars were planted at two different locations, Cikarawang and Sawah Baru Experimental Field but at the same elevation (250 m above sea level). The cultivars were scored according to morphological and physiological characters, total N and total non-structural carbohydrates (TNC), yield and yield components. There were no statistically differences in pod yield, seed yield and harvest index between the cultivars, but there were differences in dry matter distribution between cultivars. TNC content in stem correlated positively with pod ﬁ lling. Carbohydrates for pod ﬁ lling presumed were derived from dry matter accumulation in early pod ﬁ lling stage. It was concluded that the ideal growing type of peanut are early accumulated dry matter but almost no increase of dry matter accumulation in upper part of plant during seed development. Keywords: dry matter distribution, pod ﬁ lling, peanut